TGF-β1-Induced Epithelial–Mesenchymal Transition Promotes Monocyte/Macrophage Properties in Breast Cancer Cells - Johansson, Joel; Tabor, Vedrana; Wikell, Anna; Jalkanen, Sirpa; Fuxe, Jonas (Frontiers in Oncology, 2015)
Breast cancer progression towards metastatic disease is linked to re-activation of epithelial-mesenchymal transition (EMT), a latent developmental process. Breast cancer cells undergoing EMT lose epithelial characteristics and gain the capacity to invade the surrounding tissue and migrate away from the primary tumor. However, less is known about the possible role of EMT in providing cancer cells with properties that allow them to traffic to distant sites. Given the fact that pro-metastatic cancer cells share a unique capacity with immune cells to traffic in-and-out of blood and lymphatic vessels we hypothesized that tumor cells undergoing EMT may acquire properties of immune cells. To study this, we performed gene-profiling analysis of mouse mammary EpRas tumor cells that had been allowed to adopt an EMT program after long-term treatment with TGF-β1 for two weeks. As expected, EMT cells acquired traits of mesenchymal cell differentiation and migration. However, in addition, we found another cluster of induced genes, which was specifically enriched in monocyte-derived macrophages, mast cells, and myeloid dendritic cells (DCs), but less in other types of immune cells. Further studies revealed that this monocyte/macrophage gene cluster was enriched in human breast cancer cell lines displaying an EMT or a Basal B profile, and in human breast tumors with EMT and undifferentiated (ER-/PR-) characteristics. The results identify an EMT-induced monocyte/macrophage gene cluster, which may play a role in breast cancer cell dissemination and metastasis.